Social media sentiment study on COVID-19 outbreak - Karmaker, Anik; Hafiz, Nayeem Mohammad; Chanda, Anir (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.